Effect of 1α,25-Dihydroxyvitamin D3 on the Radiation Response in Prostate Cancer: Association With IL-6 Signaling - Wu, Chun-Te; Huang, Yun-Ching; Chen, Wen-Cheng; Chen, Miao-Fen (Frontiers in Oncology, 2021)
Radiotherapy (RT) is the main treatment modality for prostate cancer (PCa). This study investigated the role of IL-6 in biological sequelae following irradiation and highlighted the effects of 1α,25-dihydroxyvitamin D3 (calcitriol) on the radiation response of PCa and its relationship with IL-6 signaling. Human and murine PCa cell lines were used to examine the response to irradiation in vitro and in vivo. The relationship of IL-6 expression with clinicopathologic characteristics in 104 PCa patients treated with definite RT was also examined. We also investigated the changes in radiation response after calcitriol supplementation and the relationship between calcitriol and IL-6 signaling by conducting cellular and animal experiments. Based on clinical samples, the positivity of IL-6 staining is a significant predictor of biochemical failure-free survival for PCa patients treated with definite RT. Data from preclinical models showed that inhibition of IL-6 increased the response of PCa to radiation, which was associated with increased oxidative DNA damage, attenuated EMT and MDSC recruitment, and decreased tumor regrowth. Moreover, increased vitamin D3 levels by calcitriol supplementation or induction by UVB-radiation was associated with inhibited IL-6 signaling and increased the response to irradiation observed in animal models. These data demonstrate that IL-6 play a critical role in the radiation response of PCa, which involved tumor cell killing and altering the tumor microenvironment. Directly targeting IL-6 signaling or vitamin D3 supplement with oral or light treatment could be a promising strategy to increase the response of PCa to radiation.